2015
DOI: 10.1155/2015/293408
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Genetic Damage in Cervical Nuclei and Lymphocytes in Women with Different Levels of Dysplasia and Cancer-Associated Risk Factors

Abstract: The comet assay can be used to assess genetic damage, but heterogeneity in the length of the tails is frequently observed. The aims of this study were to evaluate genetic damage and heterogeneity in the cervical nuclei and lymphocytes from patients with different levels of dysplasia and to determine the risk factors associated with the development of cervical cancer. The study included 97 females who presented with different levels of dysplasia. A comet assay was performed in peripheral blood lymphocytes and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Recently our group (18) used migration groups (MG) as an alternative parameter to evaluate genetic damage based on the heterogeneity of the migration of comet cells. Previous studies have reported great heterogeneity of damage in the DNA of comet cells due to variations in cell size, differences in sensitivity to genotoxic or differences in the type of genetic damage manifested (19)(20)(21). The severity of cytotoxicity and mutagenicity caused by UV radiation in mammalian cells depends on the lesions produced mainly on the DNA (22).…”
Section: Introductionmentioning
confidence: 99%
“…Recently our group (18) used migration groups (MG) as an alternative parameter to evaluate genetic damage based on the heterogeneity of the migration of comet cells. Previous studies have reported great heterogeneity of damage in the DNA of comet cells due to variations in cell size, differences in sensitivity to genotoxic or differences in the type of genetic damage manifested (19)(20)(21). The severity of cytotoxicity and mutagenicity caused by UV radiation in mammalian cells depends on the lesions produced mainly on the DNA (22).…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicated that the heterogeneity of genetic damage could reflect the variation of DNA lesions from one cell to another in the same population [14]. The heterogeneity in DNA migration allowed the observation of responses of small subpopulations to various treatments [12,15] as well as its relationship with cell size, differences in sensitivity to genotoxic agents, or differences in the type of manifested genetic damage [2,10,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly,Udumudi et al., Carlos Alvarez-Moya et al, and Gandhi et al found that cervical cancer patients exhibited higher levels of DNA damage (comet tail length) than age-matched controls. Udumudi et al and Carlos Alvarez-Moya et al studied DNA damage in different stages of cervical cancer and discovered that DNA damage increased (comet tail length) as the stage of cervical cancer grew[34,48,58]. Smitha et al investigated the impact of MDA, an oxidative stress marker, in cervical cancer patients.…”
mentioning
confidence: 99%